Relating baseball seam height to carry distance - Kensrud, J. R.; Smith, L. V.; Nathan, A.; Nevins, D. (Procedia Engineering, 2015)
Past work has shown large variation in the drag of baseballs. Little is known concerning the causes of variation in ball drag. Ball diameter, weight, seam height, surface roughness, and shape influence lift and drag, and therefore carry distance. The aim of this work was to quantify the effect of seam height and roundness on ball lift and drag, which, to our understanding, has never been done outside of a wind tunnel. A bespoke, non-contact, ball surface profiler, was used to measure ball radius, including seam height. The profiles were analyzed to describe ball roundness and seam height separately. Balls with three different seam heights were projected in an enclosed stadium 102-122 m (describing a typical fly ball). Redundant radar devices were used to measure launch angle, speed, and flight paths. High speed video was used to confirm launch angle and ball spin rate. Hit distance was verified with a physical tape measure. The ball's roundness influenced the effective height of a seam. Measurements of the non-seam area of a ball were necessary to characterize the seams of a ball. A strong correlation was observed between seam height and a ball's drag coefficient. Lift, however, was not sensitive to seam height or ball shape.